2008
DOI: 10.1111/j.1468-1293.2008.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of and risk factors for MRSA bacteraemia in an HIV‐infected cohort in the HAART era*

Abstract: Objectives To define the incidence and risk factors for methicillin resistant Staphylococcus aureus (MRSA) bacteraemia in an HIV‐infected population. Methods From January 1, 2000 to December 31, 2004, we conducted a retrospective cohort study. We identified all cases of Staphylococcus aureus bacteraemia (SAB), including MRSA, among patients enrolled in the Johns Hopkins Hospital out‐patient HIV clinic. A conditional logistic regression model was used to identify risk factors for MRSA bacteraemia compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 32 publications
(33 reference statements)
3
44
0
Order By: Relevance
“…Our incidence rate estimates are lower than the estimates in these prior studies, as we included all patients, regardless of hospitalization, in the denominator. [12]. Despite the slight drop in 2008, our conclusion, based on multivariate results, is that the overall incidence of bacteraemia rose slightly during this period, especially after 2004.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our incidence rate estimates are lower than the estimates in these prior studies, as we included all patients, regardless of hospitalization, in the denominator. [12]. Despite the slight drop in 2008, our conclusion, based on multivariate results, is that the overall incidence of bacteraemia rose slightly during this period, especially after 2004.…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, methicillin-resistant Staphylococcus aureus (MRSA) infection has emerged as a significant complication among HIV-infected subjects [10][11][12][13][14].…”
mentioning
confidence: 99%
“…Several studies have reported an increased risk of MRSA colonization and infection in HIV-infected individuals compared with the general population [28][29][30][31][32]. The prevalence of MRSA in Denmark is low [16] and, correspondingly, rates were low among HIV-infected individuals and comparable to those in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A review of laboratory results demonstrated an overall mean CD4 cell count of 30 cells/mm 3 (standard deviation [SD], 31) and a mean plasma HIV RNA level of 137,520 copies/ml (SD, 267,090) during this time period. Twenty-six (81%) of the MRSA SSTIs presented at a severely immunosuppressed state (CD4, Ͻ50 cells/mm 3 ), and all 32 SSTIs (100%) occurred at an HIV plasma RNA level of Ͼ1,000 copies/ml. Poor adherence to antiretroviral therapy was noted, with only brief periods of adherence, during this period (Table 1).…”
mentioning
confidence: 99%
“…A 27-year-old African-American male was diagnosed with HIV/AIDS in September 1997 after an episode of cryptococcal meningitis and a CD4 cell count of 16 cells/mm 3 . His clinical course was complicated by antiretroviral medication nonadherence; the development of dermatologic conditions, including eosinophilic folliculitis and xerosis; esophageal candidiasis; HIV-associated wasting; and chronic renal dysfunction.…”
mentioning
confidence: 99%